Correction to: Methods for assessing the epistemic uncertainty captured in ground-motion models - Guillermo Aldama-Bustos; John Douglas; Fleur O. Strasser; Manuela Daví; Alice MacGregor (Bulletin of Earthquake Engineering, 2023)

Methods for assessing the epistemic uncertainty captured in ground-motion models - Guillermo Aldama-Bustos; John Douglas; Fleur O. Strasser; Manuela Daví; Alice MacGregor (Bulletin of Earthquake Engineering, 2023)
A key task when developing a ground-motion model (GMM) is to demonstrate that it captures an appropriate level of epistemic uncertainty. This is true whether multiple ground motion prediction equations (GMPEs) are used or a backbone approach is followed. The GMM developed for a seismic hazard assessment for the site of a UK new-build nuclear power plant is used as an example to discuss complementary approaches to assess epistemic uncertainty. Firstly, trellis plots showing the various percentiles of the GMM are examined for relevant magnitudes, distances and structural periods to search for evidence of “pinching”, where the percentiles narrow excessively. Secondly, Sammon’s maps, including GMPEs that were excluded from the logic tree, are examined to check the spread of the GMPEs for relevant magnitudes and distances in a single plot. Thirdly, contour plots of the standard deviation of the logarithms of predicted ground motions from each branch of the logic tree (σ µ ) are compared with plots drawn for other relevant hazard studies. Fourthly, uncertainties implied by a backbone GMM derived using Campbell (2003)’s hybrid stochastic empirical method are compared to those of the proposed multi-GMPE GMM. Finally, the spread of the percentile of hazard curves resulting from implementing the GMM are examined for different return periods to check whether any bands of lower uncertainty in ground-motion space result in bands of lower uncertainty in hazard space. These five approaches enabled a systematic assessment of the level of uncertainty captured by the proposed GMM.

A streamlined approach for the seismic hazard assessment of a new nuclear power plant in the UK - Guillermo Aldama-Bustos; Iain J. Tromans; Fleur Strasser; Graham Garrard; Guy Green; Liz Rivers; John Douglas; Roger M. W. Musson; Simon Hunt; Angeliki Lessi-Cheimariou; Manuela Daví; Colin Robertson (Bulletin of Earthquake Engineering, 2019)

Probabilistic seismic hazard assessment for a new-build nuclear power plant site in the UK - Iain J. Tromans; Guillermo Aldama-Bustos; John Douglas; Angeliki Lessi-Cheimariou; Simon Hunt; Manuela Daví; Roger M. W. Musson; Graham Garrard; Fleur O. Strasser; Colin Robertson (Bulletin of Earthquake Engineering, 2019)

Earthquakes from 1820 to 1936 in Grahamstown and surroundings (Eastern Cape Province, South Africa) - Paola Albini; Fleur O. Strasser; Nicolette S. Flint (Bulletin of Earthquake Engineering, 2014)

A strong-motion database from the Central American subduction zone - Maria Cristina Arango; Fleur O. Strasser; Julian J. Bommer; Douglas A. Hernández; Jose M. Cepeda (Journal of Seismology, 2011)

A strong-motion database from the Peru–Chile subduction zone - Maria C. Arango; Fleur O. Strasser; Julian J. Bommer; Ruben Boroschek; Diana Comte; Hernando Tavera (Journal of Seismology, 2011)

Ground motions observed during the 15 August 2007 Pisco, Peru, earthquake - Hernando Tavera; Isabel Bernal; Fleur O. Strasser; Maria C. Arango-Gaviria; John E. Alarcón; Julian J. Bommer (Bulletin of Earthquake Engineering, 2009)

An evaluation of the applicability of the NGA models to ground-motion prediction in the Euro-Mediterranean region - Peter J. Stafford; Fleur O. Strasser; Julian J. Bommer (Bulletin of Earthquake Engineering, 2008)

Truncation of the distribution of ground-motion residuals - Fleur O. Strasser; Julian J. Bommer; Norman A. Abrahamson (Journal of Seismology, 2008)

Style-of-Faulting in Ground-Motion Prediction Equations - Julian J. Bommer; John Douglas; Fleur O. Strasser (Bulletin of Earthquake Engineering, 2003)